Novel Two-Dimensional (2-D) Defected Ground Array for Planar Circuits - Haiwen Liu; Xiaowei Sun; Zhengfan Li (Active and Passive Electronic Components)
This paper presents a novel two-dimensional (2-D) defected ground array (DGA) for planar circuits, which has horizontal and vertical periodicities of defect structure. The defected unit cell of DGA is composed of a Sierpinski carpet structure to improve the effective inductance. Measurements show that the proposed DGA provides steeper cutoff characteristics, lower cutoff frequency, and higher slow-wave factors than the conventional periodic defected ground structure in the same occupied surface.